1996
DOI: 10.1159/000164015
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Systemic Sclerosis (SSc) Skin Grafts into Severe Combined Immunodef icient Mice: Increased Presence of SSc Leukocytes in SSc Skin Grafts and Autoantibody Production following Autologous Leukocyte Transfer

Abstract: This study was performed to evaluate the potential of the severe combined immunodeficient (Scid) mouse as a model to study the pathogenesis of systemic sclerosis (SSc). Scid mice were divided into three treatment groups: group 1 received skin grafts and autologous peripheral blood mononuclear cells (PBMC) from either SSc patients or normal individuals, group 2 received only SSc or normal skin grafts, and group 3 received only SSc or normal PBMC transfer. Antinuclear antibodies with a similar expression pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(40 reference statements)
0
0
1
Order By: Relevance
“…Previous studies have identified infiltrating T cells in the skin of dSSc patients [19], [20], [21], [22], [23], although an association between T cell gene expression and dSSc was not observed in our prior study [16]. A new result from this study is genes typically associated with T cells are more highly expressed in a subset of the patients ( Figure 1F ).…”
Section: Resultscontrasting
confidence: 49%
“…Previous studies have identified infiltrating T cells in the skin of dSSc patients [19], [20], [21], [22], [23], although an association between T cell gene expression and dSSc was not observed in our prior study [16]. A new result from this study is genes typically associated with T cells are more highly expressed in a subset of the patients ( Figure 1F ).…”
Section: Resultscontrasting
confidence: 49%